ANALISIS KURIKULUM PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI PADA TINGKAT SEKOLAH MENENGAH ATAS (SMA) DALAM MENGATASI MENTAL DISORDERS: STUDI ANALISIS KURIKULUM MERDEKA - Syarif Hidayatullah; Ziyad (Indonesian Society and Religion Research, 2025)
The Islamic religious education curriculum not only plans activities to transform knowledge, but the curriculum must be able to prepare a planning tool that can form individuals comprehensively (completely). One aspect that needs to be considered to achieve the results of curriculum implementation is the psychological aspect of students. In this area, it is one of the urgent elements to be considered because many teenagers at the Senior High School (SMA) level experience mental disorders. Therefore, a curriculum analysis is needed that can overcome mental disorders in adolescents. This type of research is library research with a content analysis method on the Islamic Religious Education (PAI) curriculum at the Senior High School (SMA) level. The results of this study indicate that the Islamic religious education curriculum at the senior high school level will be effective and efficient in overcoming mental problems by reorganizing the teaching system through preparing a positive school environment and emphasizing the substance of learning in the realm of faith that can strengthen students' beliefs and implementation in the form of worship in the aspect of fiqh such as prayer and praying. It contains elements of catharsis as a form of individual release and tension, and no less important is the emphasis on the moral aspect that will become a moral value that contains positive imitation that will affect the surrounding environment. Forming good cooperation between families, communities, and educational institutions will provide positive role models in both religious and social activities that will unconsciously be able to overcome mental crises in adolescence.